Bahasa Inggris Bahasa Inggris - Alfarid Kurnialandi; Elviera Gamelia; Siti Masfiah (BPSDMP KOMNFO Yogyakarta, Kementerian Komunikasi dan Informatika, 2023)
This study aims to determine the effect of gender, socioeconomic status, social support, TikTok usage duration, TikTok body shape content exposure, and TikTok user activity level on body image. We try to combine theory from Cash and Pruzinski (2002), Grogan (2001), and uses and effects theory by Sven Windahl (1979) to identify various variables (including TikTok) that can affect body image. This research is quantitative cross-sectional. It involved 220 students taken from the population of 19,992 students using an incidental sampling technique. Data analysis used univariate, bivariate (chi-square), and multivariate (multiple logistic regression). Variables related to body image are social support (p = 0.033), body shape content exposure (p = 0.001), and user activity level (p = 0.00). The Variable that affects body image is the user activity level in the low-high category (p = 0.005, OR = 10.644).